Legal Analysis of Criminal Liability for Theft of State-Owned Enterprise Assets: A Study of Pekanbaru District Court Decision Number 1008/Pid.B/2025/PN Pbr - Milda Wahyuni; Zainal Abidin Pakpahan; Muhammad Yusuf Siregar (CV. Social Politic Genius (SIGn), 2026)
This research is motivated by the phenomenon of crimes against state vital infrastructure components, which are frequently subjected to minimalist sentencing decisions by judicial institutions, thereby undermining the protection of public strategic assets. The primary problem in this study centers on the anomaly of sentencing disparity in Decision Number 1008/Pid.B/2025/PN Pbr. In this case, the criminal act of dismantling the bolts of a transmission tower owned by PT PLN was only punished with a criminal sanction of one year and ten months of imprisonment. The objective of this research is to dogmatically analyze the offender’s criminal liability based on Article 363 section (1) point 5 juncto Article 64 section (1) of the Penal Code, and to criticize the rationality of the judge’s reasoning applying the rehabilitative theory (verbeteringstheorie) to an adult offender. Utilizing the normative juridical research method with a case and statute approach, legal materials were analyzed qualitatively and normatively through deductive syllogistic reasoning. The research results indicate that the public prosecutor successfully proved all elements of aggravated theft and of a continuous act. However, a systemic failure was discovered, originating in the public prosecutor’s low criminal demand, which was subsequently exacerbated by the judge’s logical-reasoning fallacy in manipulating the profile of the 37-year-old defendant as a young individual to justify leniency. The research conclusion affirms that the application of the rehabilitative theory to a mature adult executing a premeditated crime repetitively injures public justice and undermines the deterrent function of criminal law. The implications of this research demand a paradigm shift for law enforcement officers and the issuance of specific prosecution guidelines to ensure maximum protection of national vital objects.